Monetary and financial integration in East Asia: the relevance of european experience - Park, Yung Chul.; Wyplosz, Charles; European Commission : Directorate-General for Economic and Financial Affairs (Brussels : Office for Infrastructure and Logistics in Brussels, 2008)
This report examines the process of economic and financial integration in East Asia in the light of Europe's experience. The report provides a comprehensive analysis of East Asian monetary and financial integration process (including a deep analysis of East Asia's response to the 1997-98 financial crisis), a comprehensive critical survey of the literature on monetary and financial integration in East Asia, and an assessment of the various initiatives undertaken in the region for financial cooperation and macroeconomic surveillance. Its aim is to evaluate the evolution of the last decade and to offer policy suggestions. The main policy recommendations concern essentially two areas: (i) how to promote the creation of a regional financial market in Asia and (ii) how to encourage cooperation and macroeconomic surveillance in the region. (Provisional version. The printed publication will be delayed until the final text is available).
Economic Papers.